1983
DOI: 10.1128/iai.42.2.567-573.1983
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of enhanced resistance of Mycobacterium bovis BCG-treated mice to ectromelia virus infection

Abstract: The mechanism of enhanced resistance of Mycobacterium bovis BCG-treated mice to ectromelia virus infection was investigated by determining the effect of splenectomy, antithymocyte. serum, and antimacrophage serum on resistance. It was greatly reduced by these treatments, not only in normal mice, but also in mice treated with live or heat-inactivated BCG. Production of circulating interferon by ectromelia virus and Newcastle disease virus was augmented in BCG-treated mice and was markedly depressed by splenecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The first is that heterologous immunity can be demonstrated between mycobacteria and viruses. Earlier reports had indicated that BCG or M. tuberculosis infection provided resistance in mice to VV or ectromelia virus, but in those studies the virus challenge was early after immunization, when immune responses to the mycobacteria were likely ongoing (3,16,40,44,56). In this present report, mice were treated with antibiotics to clear residual mycobacteria to minimum levels, the immune system appeared at rest (Table 1; Fig.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…The first is that heterologous immunity can be demonstrated between mycobacteria and viruses. Earlier reports had indicated that BCG or M. tuberculosis infection provided resistance in mice to VV or ectromelia virus, but in those studies the virus challenge was early after immunization, when immune responses to the mycobacteria were likely ongoing (3,16,40,44,56). In this present report, mice were treated with antibiotics to clear residual mycobacteria to minimum levels, the immune system appeared at rest (Table 1; Fig.…”
Section: Discussionmentioning
confidence: 50%
“…This indicates that these BCG-immune hosts were in a resting immune state without an overt ongoing immune response. This distinguishes this study from previous reports on resistance of BCG-infected or M. tuberculosis-infected hosts to heterologous pathogens at 7 to 21 days after exposure to the mycobacteria (3,40,44,56).…”
Section: Status Of the Bcg-induced Resting Memory Statementioning
confidence: 63%
See 1 more Smart Citation
“…Also, lower virus yields correlated with elevated interferon levels (fourto eightfold) in ascitic fluid and cultured peritoneal exudate cells or spleen cells (467). The importance of interferon in this system was further suggested by Sakuma et al (412), who showed that splenectomy of mice prior to treatment with BCG and infection with ectromelia virus (Ishibashi strain) resulted in a more severe infection and reduced levels of interferon in serum. Peritoneal exudate cells from mice treated 7 days earlier with another immunomodulator, Corynebacterium parvum, were not productively infected by ectromelia virus (Hampstead and Moscow strains), even though adsorption and penetration of the virus was unaffected (99).…”
Section: Interferonsmentioning
confidence: 90%
“…Trained immunity refers to immunological memory within the innate immune system, leading to an augmented response to subsequent, often heterologous insults (13). Innate immune memory is induced in animals after vaccination with BCG (14,15) although the precise mechanisms via which this occurs are still being studied. Studies of TB contacts show that despite high levels of exposure, up to 30-50% of individuals do not become infected with M.tb, as evidenced by non-reactive tuberculin skin tests and negative IFN-γ release assay (IGRA) testing (16).…”
Section: Trained Immunitymentioning
confidence: 99%